English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories
0

please help! lol

2007-02-06 15:56:32 · 4 answers · asked by K C 1 in Science & Mathematics Mathematics

4 answers

First multiply out the square and combine like terms inside:

7 - i(2 - 3i)² =
7 - i(2 - 3i)(2 - 3i) =
7 - i(4 - 6i - 6i + 9i²) =
7 - i(4 - 12i + 9i²) =

You know i = √-1 so i² = -1, and:

7 - i(4 - 12i + 9(-1)) =
7 - i(4 - 12i - 9) =
7 - (4i - 12i² - 9i) =
7 - (4i + 12 - 9i) =
7 - (12 - 5i) =
7 - 12 + 5i =
-5 + 5i

2007-02-06 16:24:48 · answer #1 · answered by Anonymous · 0 0

7 - i(2-3i)² =
7 - (2i +3)² =
7 - ( -4 + 12i + 9)=
2 + 12i
=
2 ( 1 + 6i)

2007-02-07 00:50:19 · answer #2 · answered by M. Abuhelwa 5 · 0 0

7-i(2-3i)^2
7-i(4-12i+9i^2)
7-i(-5-9i)
7+5i+9i^2
-2+5i

2007-02-07 00:04:16 · answer #3 · answered by yupchagee 7 · 0 0

man do your own homework there is a reason for it trust me...yahoo answers wont be there assisting you during your testing.

2007-02-07 00:00:57 · answer #4 · answered by Anonymous · 0 0

fedest.com, questions and answers